Paratextuelle Politik und Praxis Interdependenzen von Werk und Autorschaft - Gerstenbräun-Krug, Martin (2018)
This book directs the attention on the role of non-book authorial paratexts. Those are essential for constituting and establishing authorship in the literary field and the book poses the question of interpendence between work and authorship. Dynamics and genesis of work and authorship between the baroque period and today are described in theoretical, historic and empiric oriented articles.